PENGARUH SISTEM PENGENDALIAN INTERNAL, MORALITAS INDIVIDU, DAN KESESUAIAN KOMPENSASI TERHADAP PENCEGAHAN FRAUD PENGELOLAAN DANA DESA - sarah prihatin, sarah prihatin (Universitas Slamet Riyadi, 2021)
This study aims to determine the effect of internal control systems, individual morality, and suitability of compensation on the prevention of fraud in village fund management. The type of data used is quantitative data. The data source used is primary data. The technique of collecting data was by distributing questionnaires to 15 villages in the Banyudono District, Boyolali Regency. The population of this research is 60 village apparatus, financial subdivision of village fund management in Banyudono District, Boyolali Regency. The sample used in this study were 59 respondents from the financial division of village fund management. The sampling technique was carried out using the saturated sampling method. This study shows that the internal control system has a significant positive effect on the prevention of village fund management fraud, individual morality has a significant positive effect on the prevention of village fund management fraud, and the suitability of compensation has a significant positive effect on the prevention of fraud in village fund management.